Pyomyositis resulting in abscess in an infant and in osteomyelitis in a healthy teenager without fever case reports and literature review - Omer Nasiroglu; Sebastian Camargo; Mubin Khan (Elsevier, 2021)
Pyomyositis is a bacterial infection of the skeletal muscle, when diagnosis is delayed it can result in major complications. Magnetic resonance imaging should be considered in case of unexplained extremity pain with abnormal inflammatory markers. A 5-month-old infant with right thigh swelling-pain for one day and a teenage with left thigh pain and swelling for 3 days without trauma presented to emergency department. Fever was denied in both cases. Both cases radiography were noncontributory but both had elevated C-reactive protein. Magnetic resonance imaging with gadolinium did confirm the diagnosis promptly. Both did recover without any sequela. In case of unexplained extremity pain-swelling, even without fever, if patient has elevated acute phase reactants Pyomyositis should be considered in order to diagnose and treat it timely to avoid major complications.